2001
DOI: 10.5326/15473317-37-6-557
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic findings in 50 dogs with retrobulbar disease

Abstract: Records of 50 dogs with signs of retrobulbar disease that had ultrasonography and diagnosis based on results of cytopathology or histopathology were reviewed retrospectively. Abnormalities were identified ultrasonographically in 43 (86%) dogs. Mass effect was identified in 42% of dogs with neoplasia and 30% of dogs with abscess. Ten of 11 (91%) orbital bone lesions were in dogs with retrobulbar neoplasia. A cavitary lesion was recognized ultrasonographically in 75% of dogs with salivary mucocele and 50% of dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 7 publications
6
76
1
1
Order By: Relevance
“…Given the wide variety of diseases that can be encountered, advanced imaging modalities play a major role in the diagnostic and staging assessment of the lesion, guiding therapeutic decisions and monitoring or follow-up of treatment (Penninck et al, 2001;Collins et al, 2013). CT, MRI (Boroffka and Voorhout, 1999;Armour et al, 2011;Lederer et al, 2015) and ultrasound (US) have been demonstrated to be accurate in evaluating orbital disease (Mason et al, 2001;Boroffka et al, 2007). In addition, US has been demonstrated to be particularly useful in guiding interventional procedures throughout the body both in veterinary and in human patients (Phillips and Schneider, 1981;Gupta et al, 1999;Constantin et al, 2010;Orlandi et al, 2013;Spiess and Pot, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Given the wide variety of diseases that can be encountered, advanced imaging modalities play a major role in the diagnostic and staging assessment of the lesion, guiding therapeutic decisions and monitoring or follow-up of treatment (Penninck et al, 2001;Collins et al, 2013). CT, MRI (Boroffka and Voorhout, 1999;Armour et al, 2011;Lederer et al, 2015) and ultrasound (US) have been demonstrated to be accurate in evaluating orbital disease (Mason et al, 2001;Boroffka et al, 2007). In addition, US has been demonstrated to be particularly useful in guiding interventional procedures throughout the body both in veterinary and in human patients (Phillips and Schneider, 1981;Gupta et al, 1999;Constantin et al, 2010;Orlandi et al, 2013;Spiess and Pot, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies report that the presence of orbital bone lesions was suggestive of neoplasia and that other ultrasonographic findings are not specific (Mason and others 2001). For this reason further diagnostic imaging techniques are utilised for the assessment of retrobulbar disease in veterinary species including MRI and CT, either alone, or in conjunction with ocular ultrasound (Grahn and others 1993, Dennis 2000, Penninck and others 2001, Gonzalez and others 2001, Sturges and others 2006, Hecht and Adams 2010, Armour and others 2011).…”
Section: Discussionmentioning
confidence: 99%
“…2 Ultrasonography is beneficial in compromised patients because it does not require anesthesia, and it is the least expensive imaging modality. 6 Both CT and magnetic resonance imaging are superior to ultrasonography in evaluating extent of the lesion and assessing adjacent soft tissues and bony structures. 2 Computed tomography was performed in the dog of this report and allowed assessment of the full extent of the mass prior to surgery.…”
Section: Commentsmentioning
confidence: 99%